The unknown digit is 5.724
Answer:
-16
Step-by-step explanation:
Answer:
A. 1
Step-by-step explanation:
In each football game there is only 1 halftime
Hey!
To start solving equation, we should first distribute the parenthesis. We do this so that we can get rid of the parenthesis.
<em>Original Equation :</em>
3 ( x - 4 ) ≥ 5x + 2
<em>New Equation {Changed by Distribution} :</em>
3x - 12 ≥ 5x + 2
Next, we'd add 12 to both sides of the equation to get rid of the 12 on the left side of the equation.
<em>Old Equation :</em>
3x - 12 ≥ 5x + 2
<em>New Equation {Changed by Adding 12 to Both Sides} :</em>
3x ≥ 5x + 14
Now we subtract 5x from both sides of the equation to get rid of the 5x from the right side.
<em>Old Equation :</em>
3x ≥ 5x + 14
<em>New Equation {Changed by Subtracting 5x From Both Sides} :</em>
-2x ≥ 14
Now we must inverse the inequality. To do that we multiply both sides by -1.
<em>Old Equation :</em>
-2x ≥ 14
<em>New Equation {Changed by Inverse} :</em>
2x ≤ -14
Just by looking at the equation, you can easily tell that it needs to be simplified. So, that's what we'll do next.
<em>Old Equation :</em>
2x ≤ -14
<em>New Equation {Changed by Dividing Both Sides by Two} :</em>
x ≤ -7
Seeing as the equation cannot be simplified any further, we have our answer.
<em>The value of x in the inequality </em><span><em>of 3 ( x – 4 ) ≥ 5x + 2, is </em> x </span>≤ -7.
Hope this helps!
- Lindsey Frazier ♥